Pengaruh Strategi Pemasaran Media Sosial Terhadap Peningkatan Pendapatan UMKM - Anggraini, Dwi Pertiwi; Suginam, Suginam; Ningsih, Trans (Journal of Business and Economics Research (JBE), 2025)
Marketing strategies using social media are currently very necessary considering the increasingly developing information technology. The lack of use of social media as promotional media for MSMEs also reduces the existence of these businesses among consumers. The aim of this research is to determine the effect of social media marketing strategies on increasing MSME income. The population in this study were all MSME actors in several villages in Tanjung Morawa District, namely 672 MSMEs with a sample of 20 MSME businesses taken randomly. The data collection technique in this research is by using a questionnaire. And the data analysis technique used is to carry out simple regression analysis. The results of the tests that have been carried out show that the t value for the social media marketing strategy variable is 4.286 > t table 1.734 and the significant value is 0.005 < 0.05, so Ho is rejected and Ha is accepted, thus partially the social media marketing strategy has a positive and significant effect on increasing MSME income. . The R square value is 0.427 or 42.7%. This means that the social media marketing strategy is able to explain its presence in increasing MSME income by 42.7%, while the remaining 57.3% is explained by other variables not examined in this research.